Selection of Suitable Reference Genes for Quantitative Real-time PCR in Sapium sebiferum - Chen, Xue; Mao, Yingji; Huang, Shengwei; Ni, Jun; Lu, Weili; Hou, Jinyan; Wang, Yuting; Zhao, Weiwei; Li, Minghao; Wang, Qiaojian; Wu, Lifang (Frontiers in Plant Science, 2017)
Chinese tallow (Sapium sebiferum L.) is a promising landscape and bioenergy plant. Measuring gene expression by quantitative real-time polymerase chain reaction (qRT-PCR) can provide valuable information on gene function. Stably expressed reference genes for normalization are a prerequisite for ensuring the accuracy of the target gene expression level among different samples. However, the reference genes in Chinese tallow have not been systematically validated. In this study, 12 candidate reference genes (18S, GAPDH, UBQ, RPS15, SAND, TIP41, 60S, ACT7, PDF2, APT, TBP and TUB) were investigated with qRT-PCR in 18 samples, including those from different tissues，from plants treated with sucrose and cold stresses. The data were calculated with four common algorithms, geNorm, BestKeeper, NormFinder, and the delta cycle threshold (ΔCt). TIP41 and GAPDH were the most stable for the tissue-specific experiment, GAPDH and 60S for cold treatment, and GAPDH and UBQ for sucrose stresses, while the least stable genes were 60S, TIP41, and 18S respectively. The comprehensive results showed APT, GAPDH, and UBQ to be the top-ranked stable genes across all the samples. The stability of 60S was the lowest during all experiments. These selected reference genes were further validated by comparing the expression profiles of the chalcone synthase gene in Chinese tallow in different samples. The results will help to improve the accuracy of gene expression studies in Chinese tallow.